2018
DOI: 10.1088/1742-5468/aaeb43
|View full text |Cite
|
Sign up to set email alerts
|

q-deformed fermion in many-particle systems and its application to BCS theory

Abstract: In recent decades, there have been increasing interests in quantum statistics beyond the standard Fermi-Dirac and Bose-Einstein statistics, such as the fractional statistics, quon statistics, anyon statistics and quantum groups, since they can provide some new insights into the cosmology, nuclear physics and condensed matter. In this paper, we study the many-particle system formed by the q-deformed fermions (q-fermion), which is realized by deforming the quantum algebra of the anticommutation relations. We inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…At zero temperature, the behaviors in the BCS regimes (or a superconducting model) has been studied in ref. [53]. It has been found that the breached T c as a function of 1/(k F a) of polarized q-Fermi gases with either fixed q or p. In the left panel, q is fixed to be 0.5, while in the right panel p is fixed to be 0.6.…”
Section: Numerical Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…At zero temperature, the behaviors in the BCS regimes (or a superconducting model) has been studied in ref. [53]. It has been found that the breached T c as a function of 1/(k F a) of polarized q-Fermi gases with either fixed q or p. In the left panel, q is fixed to be 0.5, while in the right panel p is fixed to be 0.6.…”
Section: Numerical Analysismentioning
confidence: 99%
“…For details, please refer to Ref. [53]. At very low temperature, we self-consistently assume that the pairing between q-fermions with different spins may occur and lead to the fermionic condensation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been intensive studies on the ideal many-quon systems [34][35][36][37][38][39][40][41][42][43][44]. In our recent paper [45], we successfully constructed a q-deformed many-body theory, the q-deformed BCS theory, for the most famous interacting fermionic system, the superconductor. By applying it to the q-deformed interacting Fermi gases, we obtained some interesting physical predictions [46].…”
Section: Introductionmentioning
confidence: 99%